2021
DOI: 10.1186/s12879-021-06927-6
|View full text |Cite
|
Sign up to set email alerts
|

Number of doses of Measles-Mumps-Rubella vaccine applied in Brazil before and during the COVID-19 pandemic

Abstract: Background Due to the social isolation measures adopted in an attempt to mitigate the risk of transmission of SARS-CoV-2, there has been a reduction in vaccination coverage of children and adolescents in several countries and regions of the world. Objective Analyze the number of doses of vaccine against Measles-Mumps-Rubella (MMR) applied before and after the beginning of mitigation measures due to COVID-19 pandemic in Brazil. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 32 publications
1
24
0
8
Order By: Relevance
“…In the period between the end of 2019 and the spring of 2022, the COVID-19 pandemic significantly influenced interpersonal contacts, which also have different impacts on measles, mumps and rubella vaccination efforts and burden across the world. For example, Brazil reported a reduction in the number of MMR vaccine doses [ 6 ], while interestingly, Japan reported de-creased estimated annual burdens in 2020 for measles (98%), mumps (47%) and rubella (94%) compared with those in 2019 due to social distances in COVID-19 pandemic [ 7 ]. However, due to the current burden of COVID-19 on public health institutions, one may expect a decrease in vaccination coverage and potential new outbreaks in near future.…”
Section: Introductionmentioning
confidence: 99%
“…In the period between the end of 2019 and the spring of 2022, the COVID-19 pandemic significantly influenced interpersonal contacts, which also have different impacts on measles, mumps and rubella vaccination efforts and burden across the world. For example, Brazil reported a reduction in the number of MMR vaccine doses [ 6 ], while interestingly, Japan reported de-creased estimated annual burdens in 2020 for measles (98%), mumps (47%) and rubella (94%) compared with those in 2019 due to social distances in COVID-19 pandemic [ 7 ]. However, due to the current burden of COVID-19 on public health institutions, one may expect a decrease in vaccination coverage and potential new outbreaks in near future.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the regional differences in the reduction of CGD visits, recent studies assessed children's low vaccination coverage during the covid-19 pandemic in Brazil, with great impact in the Northeast region compared to the South 16,26 . This result reflects the incidence and mortality rates from covid-19.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the coronavirus disease 2019 (COVID-19) pandemic, routine healthcare services, including delivery of vaccinations, were disrupted in many countries, while in some cases vaccination appointments were missed because of fear of attending healthcare facilities. Preliminary studies have demonstrated decreased routine vaccination rates in children in several countries [1] , [2] , [3] . On July 15, 2021 the World Health Organization (WHO) released global vaccination rates data for the year 2020 [4] .…”
Section: Introductionmentioning
confidence: 99%
“…We should remember however, that one solution does not fit all. Road maps with timelines and accountability metrics are needed to provide catch-up vaccinations targeting eligible age-groups and populations with higher immunity gaps and should be widely published [1] , [2] , [14] . Mobile vaccination teams and delivery of vaccinations along with other services (e.g., maternity healthcare, school-based vaccinations) may facilitate vaccinations in more deprived and remote communities, and have proven useful [7] , [10] .…”
Section: Introductionmentioning
confidence: 99%